2022
DOI: 10.1007/s40273-022-01140-y
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Non-Alcoholic Steatohepatitis: A Systematic Review

Abstract: BackgroundThe global prevalence of non-alcoholic steatohepatitis (NASH) is increasing, such that NASH is predicted to become the leading cause of liver transplantation (LT) in the US by 2025. Despite this, data on the economic burden of NASH are limited. Objectives This systematic literature review aimed to summarise and critically evaluate studies reporting on the economic burden of NASH and identify evidence gaps for subsequent research. Methods Medline, EMBASE, the Cochrane Library and EconLit were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…18 Economic impact increases with NASH severity and is anticipated to grow as the NASH population expands. 19 In the US, NASH prevalence is forecasted to rise by 63% from 16.5 million cases in 2015 to 27 million cases by 2030. 5,20 NASH cirrhosis is the most rapidly increasing cause of liver transplantation in the US.…”
Section: Impact Of Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Economic impact increases with NASH severity and is anticipated to grow as the NASH population expands. 19 In the US, NASH prevalence is forecasted to rise by 63% from 16.5 million cases in 2015 to 27 million cases by 2030. 5,20 NASH cirrhosis is the most rapidly increasing cause of liver transplantation in the US.…”
Section: Impact Of Nafldmentioning
confidence: 99%
“…The economic impact of NAFLD in the US is substantial, with estimated direct medical costs of $103 billion per year 18 . Economic impact increases with NASH severity and is anticipated to grow as the NASH population expands 19 . In the US, NASH prevalence is forecasted to rise by 63% from 16.5 million cases in 2015 to 27 million cases by 2030 5,20 .…”
Section: Impact Of Nafldmentioning
confidence: 99%
“…The most recent reviews of NITs in T2D concluded unanimously that there is an unmet need to perform specific prospective studies in outpatients with T2D, using head-to-head comparison, to compare the numerous blood and imaging tests already available in subjects at risk of MASLD. 1,2,[5][6][7][8][9][10][11]27 Here, despite limitations, we succeed to address several unmet needs: first, a prospective head-to-head comparison of widespread NITs focusing in patients with T2D; second, we optimised the performance of an already validated NashFibroTest TA B L E 2 Diagnostic performances of optimised NashFibroTest-T2D versus original NashFibroTest.…”
Section: Discussionmentioning
confidence: 99%
“…MASLD is underdiagnosed in real‐world clinical settings despite the numerous non‐invasive‐tests (NITs) available, with a high demand for diagnosis and monitoring tests 5‐11 . Differences in the use of different diagnostic tests were also seen depending on the country, with more frequent use of liver biopsy, Nash‐FibroTest, NAFLD fibrosis score, NAFLD activity score and enhanced liver fibrosis score, and less frequent use of FibroScan and some laboratory tests ( e.g ., gamma‐glutamyl‐transpeptidase [GGT] and lipid profile) reported in the United States than European countries 11 …”
Section: Introductionmentioning
confidence: 99%
“…Approximately 22.5% of NASH patients will develop hepatocellular carcinoma, and 20% will develop cirrhosis [ 8 , 9 , 10 , 11 ]. This progressive feature makes NASH the second most prevalent cause of liver transplantation in the USA [ 12 ].…”
Section: Introductionmentioning
confidence: 99%